Penyuluhan Budidaya Magot Sebagai Pakan Alternatif Ada Budidaya Ikan Gurami di Kecamatan Negara Kabupaten Jembrana Provinsi Bali - Ni Putu Diah Pradnyawati; Ganjar Wiryati; Toni Ruchimat (Unri Conference Series: Community Engagement, 2021)
Magot is a larva of the insect Hermetia illucens that can convert organic waste into high protein. Magot can be used as one of the alternative feeds of gourami fish that has a protein content equivalent to pellet feed. This is very necessary by cultivators in the Negara District who have problems regarding the increasingly high price of pellets causing high operational costs and Lack of Knowledge of Skills and Attitude of cultivators towards alternative feed that can substitute the pellet feed. The assistance of this group was carried out for approximately 3 months at POKDAKAN Mina Harapan. The purpose of this activity, which is to increase the knowledge of cultivator attitude skills on the application of BSF maggot as an alternative feed for gourami fish. The type of data collected in the form of primary data and secondary data, data collection is done through observation and interview. Data collected in qualitatively denitrifying analysisThe result of this activity is an increase in knowledge and target skills regarding magot culture and changes in the target to positive direction regarding the material provided. The addition of maggot as an alternative feed in dempond activities can be projected into 10 months of maintenance then the profits obtained using maggot BSF as an alternative feed of Rp 6,020,420, while if only using the benefits obtained in 10 months amounted to Rp 3,471,000 with 500 fish scattered.